2005
DOI: 10.1038/nrn1648
|View full text |Cite
|
Sign up to set email alerts
|

Cortical inhibitory neurons and schizophrenia

Abstract: Impairments in certain cognitive functions, such as working memory, are core features of schizophrenia. Convergent findings indicate that a deficiency in signalling through the TrkB neurotrophin receptor leads to reduced GABA (gamma-aminobutyric acid) synthesis in the parvalbumin-containing subpopulation of inhibitory GABA neurons in the dorsolateral prefrontal cortex of individuals with schizophrenia. Despite both pre- and postsynaptic compensatory responses, the resulting alteration in perisomatic inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

74
1,804
5
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,115 publications
(1,895 citation statements)
references
References 113 publications
74
1,804
5
12
Order By: Relevance
“…The neuronal effects of mutant hDISC1 are similar to some neuropathological features of schizophrenia, including increased volumes of the ventricles and reduced length of dendrites in cortex and hippocampus. 35,36,54 The present neuronal effects are also in agreement with previous in vitro experiments Figure 7 The behavioral effects of mutant hDISC1. (a) Expression of mutant hDISC1 produced significant spontaneous hyperactivity in male but not female mice.…”
Section: Discussionsupporting
confidence: 91%
“…The neuronal effects of mutant hDISC1 are similar to some neuropathological features of schizophrenia, including increased volumes of the ventricles and reduced length of dendrites in cortex and hippocampus. 35,36,54 The present neuronal effects are also in agreement with previous in vitro experiments Figure 7 The behavioral effects of mutant hDISC1. (a) Expression of mutant hDISC1 produced significant spontaneous hyperactivity in male but not female mice.…”
Section: Discussionsupporting
confidence: 91%
“…While the exact cause of hippocampus hyperexcitability in schizophrenia is unknown, correlative evidence in clinical and preclinical studies points to reduced numbers of GABAergic interneurons that express the calcium binding protein PV. These fast firing interneurons are known to maintain the oscillatory activity of excitatory glutamatergic pyramidal neurons through perisomatic targeting (Lewis et al, 2005;Lodge et al, 2009). Moreover, studies have further shown that attenuation of hyperactivity of neurons in the ventral hippocampus via drug treatment or deep brain stimulation can normalize the enhanced dopamine neuron activity, thereby reversing an augmented locomotor response to amphetamine seen in animal models of schizophrenia (Gill et al, 2011;.…”
Section: Gaba-ergic Cell Grafts For Treating Schizophreniamentioning
confidence: 99%
“…In particular, fast-spiking parvalbumin (PV)-positive inhibitory neurons, which represent 5% of all cortical neurons, are strongly affected. Reduced expression of GAD67, the main isoform synthesizing GABA in brain, is one of the most replicated findings in schizophrenia post mortem brain studies (Benes and Berretta, 2001; Lewis et al, 2005), and single nucleotide polymorphisms in the regulatory region of Gad1 (the gene coding for GAD67) are associated with childhood onset of schizophrenia (Rapoport et al, 2005). The decrease in GAD67 occurs primarily in the subset of inhibitory interneurons expressing the calcium binding protein parvalbumin (Beasley and Reynolds, 1997;Hashimoto et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…The decrease in GAD67 occurs primarily in the subset of inhibitory interneurons expressing the calcium binding protein parvalbumin (Beasley and Reynolds, 1997;Hashimoto et al, 2003). This apparent "loss of GABAergic phenotype" in PVinterneurons led to the suggestion that dysfunction of these fast-spiking inhibitory interneurons may be a core feature of the disease (Lewis et al, 2005). Whether these deficiencies are a consequence or a cause of the disorder is, however, a matter of debate.…”
Section: Introductionmentioning
confidence: 99%